Association Between Availability of a Price Transparency Tool and Outpatient Spending - Desai, Sunita; Hatfield, Laura A; Hicks, Andrew L; Chernew, Michael E; Mehrotra, Ateev (JAMA : the journal of the American Medical Association, 2016)
There is increasing interest in using price transparency tools to decrease health care spending. To measure the association between offering a health care price transparency tool and outpatient spending. Two large employers represented in multiple market areas across the United States offered an online health care price transparency tool to their employees. One introduced it on April 1, 2011, and the other on January 1, 2012. The tool provided users information about what they would pay out of pocket for services from different physicians, hospitals, or other clinical sites. Using a matched difference-in-differences design, outpatient spending among employees offered the tool (n=148,655) was compared with that among employees from other companies not offered the tool (n=295,983) in the year before and after it was introduced. Availability of a price transparency tool. Annual outpatient spending, outpatient out-of-pocket spending, use rates of the tool. Mean outpatient spending among employees offered the tool was $2021 in the year before the tool was introduced and $2233 in the year after. In comparison, among controls, mean outpatient spending changed from $1985 to $2138. After adjusting for demographic and health characteristics, being offered the tool was associated with a mean $59 (95% CI, $25-$93) increase in outpatient spending. Mean outpatient out-of-pocket spending among those offered the tool was $507 in the year before introduction of the tool and $555 in the year after. Among the comparison group, mean outpatient out-of-pocket spending changed from $490 to $520. Being offered the price transparency tool was associated with a mean $18 (95% CI, $12-$25) increase in out-of-pocket spending after adjusting for relevant factors. In the first 12 months, 10% of employees who were offered the tool used it at least once. Among employees at 2 large companies, offering a price transparency tool was not associated with lower health care spending. The tool was used by only a small percentage of eligible employees.